WAYS OF PRONOUNCING [Θ] AND [S] SOUNDS CORRECTLY - Siddikova Durdona, Siddikova Durdona Mukhtorovna (Журнал иностранных языков и лингвистики, 2021)
This article provides explanations for pronouncing [θ] sound correctly, for various positions which [θ] sound and [s] sound might be mispronounced. Furthermore, it helps to prevent from mispronouncing [θ] sound giving examples where necessary.